Psychosocial factors associated with complicated grief in caregivers during COVID-19: Results from a preliminary cross-sectional study. Issue 6 (3rd July 2022) - Bovero, Andrea; Pidinchedda, Alexa; Clovis, Federica; Berchialla, Paola; Carletto, Sara
Abstract: The COVID-19 pandemic has changed how end-of-life ceremonies are performed, affecting grief processing and bereavement experiences. In this study, caregivers of patients who died with COVID-19 during the first wave of the pandemic were asked to complete an online survey designed to detect psychosocial factors associated with the presence of complicated grief (CG). The results show CG present in 48.4% of caregivers. The marital and cohabitant status during lockdown, the perceived sense of guilt and depression levels were significantly associated with the presence of CG, whereas attendance at the funeral and social support were found to be significant protective factors.